Patients, caregivers and health‐care professionals' experience with an interdisciplinary intervention for people with multimorbidity in primary care: A qualitative study. (8th February 2020) - Ngangue, Patrice Alain; Forgues, Catherine; Nguyen, Tu; Sasseville, Maxime; Gallagher, Frances; Loignon, Christine; Stewart, Moira; Belle Brown, Judith; Chouinard, Maud‐Christine; Fortin, Martin
Abstract: Background: Multimorbidity challenges the health‐care system and requires innovative approaches. In 2015, a 4‐month patient‐centred interdisciplinary pragmatic intervention was implemented in primary care with the aim of supporting self‐management for patients with multimorbidity. Objective: To explore the perceptions and experiences of health‐care professionals, patients and their caregivers with a 4‐month patient‐centred interdisciplinary pragmatic intervention in primary care. Design: A descriptive, qualitative study using semi‐structured interviews was conducted. Setting and participants: A purposive sample of 30 participants was recruited from seven family medicine groups including patients, caregivers and health‐care professionals (HCPs). Interviews were analysed using Thorne's interpretive description approach. Results: Findings were grouped into the benefits and challenges of participating in the intervention. The programme allowed patients to adopt realistic and adapted objectives; to customize interventions to the patient's reality; and to help patients gain confidence, improve their knowledge, skills and motivation to manage their condition. Interprofessional collaboration eased the exchange of information via team meetings and electronic medical records. Challenges were related to collaboration, communication, coordination of work and integration of newly relocated HCPs mainly due to part‐time assignments and staff turnover. HCPs part‐time schedules limited their availability and hindered patients' follow‐up. Discussion and conclusion: This intervention was useful and rewarding from the HCPs, patients and caregivers' perspective. However, to ensure the success of this complex interdisciplinary intervention, implementers and managers should anticipate organizational barriers such as availability and time management of relocated HCPs.